Forum 1: Pseudoscience in healthcare - Nordin, Musa Mohd; Kheng, Khor Swee; Akhter, Muhammad Wajid; Mohd Haris, Ahmad Firdaus (International Journal of Human and Health Sciences (IJHHS), 2022)
According to the Merriam-Webster dictionary, pseudoscience is defined as “a system of theories, assumptions, and methods erroneously regarded as scientific”. In simpler terms, it is fake science made to appear like real science. Pseudoscience is rife in healthcare as it is a cash cow for unscrupulous businesses. Pseudoscience in healthcare goes hand in hand with infodemic, which according to WHO - “too much information including false or misleading information in digital and physical environments during a disease outbreak”. The trouble with pseudoscience and infodemic is ever more apparent during the COVID-19 pandemic, whereby it interferes with evidence-based methods that are implemented to combat the pandemic effectively. When the community believes in pseudoscience instead of effective public health measures such as wearing masks in public places and prevention by vaccinations, the pandemic will be difficult to control. This forum aims to explore what pseudoscience claims are being peddled in Malaysia and worldwide and how it is being dealt with. It will also explore the policies available and policies that can be structured to deal with pseudoscience in healthcare. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S12